Etnomatematika Kampung Adat Takpala: Numerasi Pada Posisi Jari Tangan - Novandini, Carolin Dwija; Lalang, Andrian Runtius; Sari, Beatrix Purnama (Universitas Nusa Cendana, 2025)
The ethnomathematical excavation of the Takpala Indigenous Village community in this study focused on the position of the fingers of the indigenous people in counting. The purpose of this study was to determine the types of numbers used by indigenous peoples based on the position of the fingers in their daily lives. To find out the type of number in question, this study uses an ethnographic method. The results showed that the use of the finger position in counting carried out by the Takpala Indigenous Village community contained modulo 10 and modulo 5 (modulo 10-5). Based on the position of the fingers, the mathematical modeling is obtained in the form of: “for every and applies ”.